Analysis of misconceptions in static fluids using four-tier diagnostic test among high school students - Farida Alia, Nenden; Fitria Amalia, Irma; Adimayuda, Rizal (Insitut Pendidikan Indonesia, 2025)
This study aims to analyze students’ misconceptions in static fluid concepts using the Four-Tier Diagnostic Test instrument. Static fluid material was chosen because of its complex characteristics and its potential to generate misconceptions, particularly in the sub-concepts of hydrostatic pressure, Pascal’s law, and Archimedes’ principle. This research employed a descriptive method with a quantitative approach. The subjects of this study were 68 eleventh-grade students from a public high school in Garut Regency. The research instrument was a four-tier diagnostic test consisting of 15 items. Data were analyzed based on the combination of students’ answers at each tier to identify categories of conceptual understanding, misconception, lack of understanding, and partial understanding. The results show that, overall, 37.74% of students experienced misconceptions, 37.65% understood the concept, 14.31% did not understand the concept, and 10.30% demonstrated partial understanding. At the sub-concept level, the highest misconceptions were found in Pascal’s Law (52.20%), followed by Archimedes' Principle (41.47%), and hydrostatic pressure (25%). The highest item-level misconception occurred in question number 7 regarding the lifting force on a piston, with a percentage of 73.53%. These findings highlight the urgent need to identify and remediate students’ misconceptions, as well as the importance of implementing in-depth diagnostic instruments, such as the Four-Tier Diagnostic Test, in physics learning.